A Review of the Present Conservation Scenario of Hog Deer (Axis poreinus) in its Native Range - Biswas, Tanushree; Mathur, V. B. (Indian Forester, 2000)
Hog deer (Axis porcinus) is a special endemic to the tall moist grasslands of South and Sonth-East Asia. There are two subspecies of Hog deer, the Indian subspecies (Axis porcinus porcinus) occurring in Pakistan, Nepal, India, Bangladesh and Burma and South-East Asian subspecies (Axis porcinus annamiticus) occurring in China, Thailand, Laos, Cambodia and Vietnam. Populations of Hog deer are confined only to the flood plain of different river systems within these countries. Hog deer has a narrow range of distribution, specific habitat requirements and has not been well studied throughout its native range. In this paper, the authors have made an attempt to compile the available information on the species with a review of its current status and distribution in India. The review indicates large-scale transformations in the native range of this species mainly due to agricultural developments in the Indo-Gangetic belt. There is also a need to re-assess its present categorisation under the Indian Wildlife (Protection) Act and IUCN Red Data Book.